The Effect of Gender and Household Education Expenditure in Indonesia - Tedy Di Oria Salam; M. Shabri Abd. Majid; Taufiq C Dawood; Suriani Suriani (Research Collaboration Community (RCC), 2021)
This study empirically examines and analyzes the effect of gender on human capital investment in Indonesia. Using the logistic regression method and data sourced from 315,672 households in Indonesia, this study shows that the number of boys, the number of girls, the working status of the head of the household, and the highest education of the head of the household have a positive and significant impact on human capital investment in Indonesia. The results show that female household heads who work and invest in the cost of children's education are more significant than male household heads who also work. Higher the education level of the head of the household, the higher the income received and also investment for children. This research shows strong evidence of gender inequality in education spending that tends to be more towards girls. Based on the results obtained, development policies can consider gender differences in investment in labor and education. Increasing the school participation rate of women compared to men will increase the differentiation of the workforce by gender but also increase income inequality between men and women. Likewise, investment in education which tends to be more directed to women than men, will reduce income inequality.